PENGARUH KEBUTUHAN, SIKAP DAN PERSEPSI TERHADAP PREFERENSI KONSUMEN SURAT KABAR JAWA POS DI SURABAYA BARAT - Herawati, Wiwik (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2005)
The aim of study is to analyze the impact of atittude, perception and need on customer prefferention in Jawa Pos News paper at Surabaya. When analyze on opinion of 100 samples from population with accidental sampling technique and questionairre as tools for collecting the data, this study shows that there are significance impacts.